2023
DOI: 10.1111/head.14442
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire smoke exposure and emergency department visits for headache: A case‐crossover analysis in California, 2006–2020

Abstract: Objective To evaluate the association of short‐term exposure to overall fine particulate matter of <2.5 μm (PM2.5) and wildfire‐specific PM2.5 with emergency department (ED) visits for headache. Background Studies have reported associations between PM2.5 exposure and headache risk. As climate change drives longer and more intense wildfire seasons, wildfire PM2.5 may contribute to more frequent headaches. Methods Our study included adult Californian members (aged ≥18 years) of a large de‐identified commercial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…In the study “Wildfire Smoke Exposure and Emergency Department Visits for Headache: A Case‐Crossover Analysis in California, 2006–2020,” the authors attempt to determine effect of wildfire smoke particulate matter on headache outcomes while controlling for confounding variables such as time of year 2 . A private insurance claims database was used to identify Emergency Department (ED) visits in adult patients with headache (or a headache subtype) as one of the first three visit diagnoses, with >13,000 ED visits in California by 9,898 unique individuals included.…”
mentioning
confidence: 99%
“…In the study “Wildfire Smoke Exposure and Emergency Department Visits for Headache: A Case‐Crossover Analysis in California, 2006–2020,” the authors attempt to determine effect of wildfire smoke particulate matter on headache outcomes while controlling for confounding variables such as time of year 2 . A private insurance claims database was used to identify Emergency Department (ED) visits in adult patients with headache (or a headache subtype) as one of the first three visit diagnoses, with >13,000 ED visits in California by 9,898 unique individuals included.…”
mentioning
confidence: 99%
“…Point estimates for the association between migraine and relatively higher PM 10 or PM 2.5 ranged from 0.97 to 3.09 20,22,44,46–49 . For PM 10 and PM 2.5 , 3/3 (100%) and 10/11 (91%) of estimates, respectively, were above the null.…”
Section: Resultsmentioning
confidence: 94%
“…Given that holidays are relatively rare, this would not be expected to strongly influence results. One short‐term study met the criteria for high risk of confounding bias due to missing the critical confounder temperature, 44 while a long‐term study from 1994 did not report on the critical confounder body mass index 45 . Finally, one study scored low risk of bias by including all of the confounders listed as critical or potential 46 …”
Section: Resultsmentioning
confidence: 99%
“…Recent literature has documented worsened cognitive outcomes, 88,89 declines in mental health, 24 and increased ED visits for headaches 90 associated with exposure to wildfire smoke. For example, Cleland et al 88 assessed cognitive performance among adults and found that wildfire smoke plumes was negatively associated with the estimated attention score on the same day and one week later.…”
Section: Summary Of Health Impacts Of Wildfire Smoke Exposurementioning
confidence: 99%